Cholera El Tor in Infants below 2 Years of Age as seen in Private and Hospitalized Patients - Haroen Noerasid; Pitono Soeparto; Bing Rudianto; Hananto Wirjo; Juliati Sudanawidjaja; Soeharjono Padmodiwirjo (Indonesian Pediatric Society, 1979)
A report was made on cholera El Tor in children under 2 years of age with mute gastroenteritis admitted to the pediatric ward of the Dr. Soetomo Hospital, Surabaya. Twenty-three out of 115 cases (20%) showed positive stool cultures. A similar report was made in the same period on patients with gastroenteritis in private practice. Four out of 108 cases (3.6%) showed positive stool cultures. A brief description of the disease pattern of infantile gastroenteritis was presented. The increasing incidence of cholera, below one year was also discussed.